2018
DOI: 10.1042/bsr20181058
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of pretreatment serum γ-glutamyltranspeptidase in primary liver cancer: a meta-analysis and systematic review

Abstract: Aim: To assess the prognostic value of the pretreatment serum γ-glutamyltranspeptidase (GGT) level in patients with primary liver cancer (PLC). Methods: Relevant studies were systematically searched online on Web of Science, PubMed, and Embase databases published until 9 October 2018. The end points were overall survival (OS), recurrence-free survival (RFS), and disease-free survival (DFS). Meta-analysis was conducted using hazard ratio (HR), and its 95% confidence interval (CI) as effect measure. Results: A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…As for the association of GGT with liver cancer, one Finnish study demonstrated that patients with high serum GGT levels had an increased risk of HCC during long‐term follow‐up 14 . Moreover, high GGT level has been associated with advanced HCC, poor prognosis and a high recurrence rate once HCC develops 34,35 . Reports regarding HCC prediction in patients who underwent antiviral therapy are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…As for the association of GGT with liver cancer, one Finnish study demonstrated that patients with high serum GGT levels had an increased risk of HCC during long‐term follow‐up 14 . Moreover, high GGT level has been associated with advanced HCC, poor prognosis and a high recurrence rate once HCC develops 34,35 . Reports regarding HCC prediction in patients who underwent antiviral therapy are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…HCC is a malignant liver tumor with high incidence. Many patients are already at advanced stages when diagnosed with HCC and, therefore, unfortunately miss the optimum opportunity for surgery and have poor response of systemic chemotherapy [ 28 30 ]. Sorafenib is the most commonly used molecular targeted drug that can be taken orally to treat advanced HCC.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported on the utility of the serum GGT level as a predictive biomarker of clinical outcomes in patients with a multitude of conditions, including cardiovascular diseases, diabetes mellitus, and metabolic syndrome [4]. Moreover, serum GGT is reportedly associated with a poor prognosis in patients with liver cancer, reflecting unfavorable clinicopathological features, including vascular invasion and the tumor burden, as demonstrated in previous meta-analyses [5,6]. Subsequently, serum GGT was also found to be a significant prognostic biomarker in patients with a variety of malignant neoplasms; however, reports of serum GGT in relation to genitourinary (GU) cancer are relatively limited, and the findings among studies of renal cell carcinoma (RCC) are sometimes contradictory depending on the metastatic status of the disease [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 85%
“…Hitherto, elevated serum GGT has been studied extensively as an unfavorable prognostic biomarker in patients with liver cancer, including hepatocellular carcinoma and intrahepatic cholangiocarcinoma, on which dozens of clinical studies have been conducted. Recently, two meta-analyses demonstrated that patients with a high serum GGT level not only had a poor prognosis (in terms of overall survival, recurrence-free survival, and disease-free survival) but also had several unfavorable clinicopathological features, including vascular invasion and the tumor burden [ 5 , 6 ]. Similar findings were also reported in other organs, including the uterus [ 81 , 82 , 83 , 84 , 85 ], colorectum [ 86 ], ovaries [ 23 ], esophagus [ 87 , 88 ], breasts [ 89 , 90 ], gallbladder [ 91 ], nasopharynx [ 92 , 93 ], stomach [ 74 , 94 ], lungs [ 95 ], and pancreas [ 96 ].…”
Section: Elevation Of Serum Ggt In Patients With Gu Cancermentioning
confidence: 99%